THE MODEL AND PERFORMANCE OF PARTNERSHIP BETWEEN SEED COMPANY AND FARMERS - Dian Widi Prasetyo; Idqan Fahmi; Yossi Wibisono (School of Business, IPB University (SB-IPB), 2015)
The partnership concept is expected to be one of the ways to improve agricultural sector in Indonesia, so that it will become a mutually beneficial partnership. One of the business entities in seed and supplier for horticultural crops is CV Rahmat Tani. However, the research has found some problems in the partnership system between CV Rahmat Tani and its farmers. Some of them are the products’ qualities which have no standard and the low price. The aims of this study were 1) to describe and evaluate the partnership that has been used by CV Rahmat Tani and partner farmers, 2) to analyze the farmers’ perception on the partnership’s implementation partnership, 3) to analyze CV Rahmat Tani’s perception on the partnership’s implementation and 4) to formulate strategies to improve the partnership’s performance. The tools of analysis used were gap analysis, EPA, and Mann Whitney Test. The result of the study showed that the pattern that tied the CV and its farmers was informal model. According to partner farmers’ perception, the priorities were 1) the delivery of seeds, pesticides, and fertilizers, 2) seeds selling price 3) cultivation and seeds management training and 4) post–harvest payment. The main priority that would be improved based on the owner’s opinion was the field supervisors’ inputs and recommendation. The recommendation strategies to improve the partnership are: 1) CV Rahmat Tani and its farmers together need to optimize planning; 2) the CV needs to provide trainings about cultivation and postharvest, and to oversee the quality of seed; 3) the CV needs to socialize the postharvest payment deadline; and 4) both parties should synchronize their perception and set some rules.Keywords: EPA, gap analysis, partnerships, seedABSTRAKKonsep kemitraan diharapkan menjadi salah satu cara untuk meningkatkan sektor pertanian di Indonesia sehingga ini akan menjadi sebuah hubungan yang menguntungkan. Salah satu badan usaha yang bergerak dibidang pembenihan dan supplier untuk tanaman hortikultura adalah CV Rahmat Tani. Namun, kerja sama tersebut dikhawatirkan akan menimbulkan sesuatu yang tidak diinginkan, misalnya kualitas barang tidak standar dan harga yang rendah. Tujuan dari penelitian ini adalah 1) mendeskripsikan dan mengevaluasi kemitraan yang telah terjalin antara CV Rahmat Tani dan petani mitra, 2) menganalisis persepsi petani terhadap pelaksanaan kemitraan, 3) menganalisis persepsi CV Rahmat Tani terhadap pelaksanaan kemitraan, dan 4) merumuskan strategi untuk meningkatkan kinerja kemitraan. Alat analisa yang digunakan adalah Servqual, EPA, dan Mann Whitney Test. Hasil penelitian menunjukkan bahwa pola kemitraan yang terjalin antara CV dan petani mitra adalah unit usaha bersama dengan sistem kontrak lisan. Menurut persepsi petani mitra, prioritas perbaikan kemitraan adalah 1) pengiriman benih, obat-obatan dan pupuk, 2) harga jual benih, 3) pelatihan dan manajemen budi daya benih, dan 4) pembayaran pascapanen. Prioritas utama yang akan ditingkatkan menurut pemilik adalah rekomendasi dan saran dari pengawas lapang. Kelima prioritas utama ini perlu diperbaiki guna mengoptimalkan kemitraan.Keywords: EPA, gap analysis, kemitraan, benih